The relationship of zinc and copper with stage in non-small cell cancer of the lung - Chetty, Dinoshan Namasivayan (My University, 2011)
Objective Several studies have shown that serum copper concentrations are higher in various carcinomas when compared to a healthy population; owing to their role as an inflammatory marker. Zinc acts as a cellular growth protector and it has been demonstrated that its deficiency is involved in several stages of malignant cell transformation. However, the usefulness of the serum zinc and copper determinations in cancer prevention, detection, treatment monitoring and prognosis require further investigation. The aim of this study is to demonstrate the diagnostic and prognostic significance of serum zinc levels (SZL) and serum copper levels (SCL), and the copper/zinc (Cu/Zn) ratio, in non-small cell lung cancer (NSCLC). Materials and Methods Thirty-four patients with NSCLC were prospectively identified, prior to treatment, over a period of one calendar year (February 2003 - January 2004) at the Department of Radiation Oncology, Johannesburg General Hospital (now Charlotte Maxeke Johannesburg Academic Hospital) and the University of the Witwatersrand. SCL and SZL were measured using atomic absorption spectroscopy (AAS) and the Cu/Zn ratio was calculated. Results SCL shows an increase (mean SCL were 0.66mg/L, 0.74mg/L and 0.76mg/L for stage II, III and IV respectively) (P=0.0897); and SZL shows a decrease (0.70mg/L,0.63mg/L and 0.62mg/L for stage II, III and IV respectively) (P=0.199) with advancing stage. The levels of both these trace elements are much lower than the reference range for a normal population. The Cu/Zn ratio increases with stage (0.995, 1.308 and 1.441 for stage II, III and IV respectively). The results were not statistically significant, but a definite trend could be observed. In addition, marked differences were noted between early stages (II) and advanced stages (III and IV) of the disease. Conclusion The lower levels of both trace elements, when compared to a reference range, are an indication of the low levels of immunity and poor general condition of patients with NSCLC (with particular reference to the author‟s institution). A clear trend could be demonstrated of increasing SCLs and decreasing SZLs with progressive stages in NSCLC. The Cu/Zn ratio also reflects similar findings in relation to stages of the disease. The results were not statistically significant, although this can be attributed to a small sample size. While trace element levels and the Cu/Zn ratio cannot be advocated as a tumour marker and prognostic variable for NSCLC at present, they do merit further study, especially in a resource constrained environment, as a simple and inexpensive diagnostic and prognostic test.
Keywords: Lung Neoplasms